Strengthening Spiritual Character through Tauhid-Based Learning in Integrated Islamic Kindergarten - Aeni, Nur; Sabani, Fatmaridah; Subhan, Subhan (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
Tauhid-based education plays a crucial role in shaping the spiritual character of young children. This study aims to analyze the implementation of tauhid learning and its influence on the development of children's spiritual character at Waladun Shalih Integrated Islamic Kindergarten in Palopo City. A qualitative case study approach was employed to gain an in-depth understanding of tauhid-oriented educational practices within an integrated Islamic school environment. Data were collected through observation, in-depth interviews, and documentation, involving the principal, teachers, staff, and group B children (aged 5–6 years) as research subjects. The findings reveal that tauhid learning is implemented in a structured manner through thematic approaches and daily spiritual activities such as collective prayer, Dhuha prayer, morning dhikr, and the introduction of Asmaul Husna. Teachers serve as role models in spirituality and behavior, functioning as direct media for instilling tauhid values. The formation of children's spiritual character is further supported by a religious school environment and active parental involvement through parenting programs. These results affirm that the implementation of tauhid learning significantly contributes to building the foundation of faith and spiritual character in early childhood